2014
DOI: 10.1111/acer.12418
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Insulin Resistance in the Protective Effect of Metformin Against Alcoholic Liver Injury

Abstract: EtOH exposure induces hepatic insulin resistance. Metformin improved insulin resistance and reversed liver injury through the activation of AMPK and normalized adiponectin signaling making metformin a promising drug for the treatment of ALD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Similar effects were caused by ethanol consumption in the decreasing hepatic PGC1α [46], and triggering reactive oxygen species (ROS) production and iron overload in the liver [47]. In fact, Zhong et al .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similar effects were caused by ethanol consumption in the decreasing hepatic PGC1α [46], and triggering reactive oxygen species (ROS) production and iron overload in the liver [47]. In fact, Zhong et al .…”
Section: Discussionmentioning
confidence: 81%
“…It was shown that fructose underwent a Maillard reaction, promoting lipid peroxidation and mitochondrial damage, and decreasing the mitochondrial-biogenic proteins, e.g., PGC1α in the liver [15] , [36] . Similar effects were caused by ethanol consumption in the decreasing hepatic PGC1α [46] , and triggering reactive oxygen species (ROS) production and iron overload in the liver [47] . In fact, Zhong et al .…”
Section: Discussionmentioning
confidence: 84%
“…In one study, a group of rats with chronic ethanol consumption showed a reduction in AMPK enzyme, but the group with ethanol consumption and treated with metformin showed improvement in hepatic injury through activation of AMPK. The AMPK level was similar in rats without metformin and without alcohol consumption [38]. Among heavy alcohol drinkers, the protective effect for HNC observed in diabetic metformin users might be explained by activation of AMPK by metformin, but further studies should carried out to evaluate and understand this mechanism.…”
Section: Discussionmentioning
confidence: 91%
“…AMPK is a cellular energy sensor enzyme that, when activated, reduces lipid synthesis, promotes fat oxidation, and inhibits gluconeogenesis . Several studies have shown that metformin treatment of alcohol‐fed mice reduces hepatic steatosis . Zhu et al .…”
Section: Ald Therapeutics That Target Irmentioning
confidence: 99%
“…127 Several studies have shown that metformin treatment of alcohol-fed mice reduces hepatic steatosis. [128][129][130] Zhu et al fed alcohol by oral gavage to male Wistar rats with or without metformin twice daily for 16 weeks and found improvement in liver enzymes, hepatomegaly, and IR in the rats treated with metformin compared with rats that did not receive metformin. These improvements were associated with increases in hepatic AMPK and insulin receptor gene expression, and support the findings of Tomita et al, who demonstrated that administration of AICAR (an AMPK activator) to male Wistar rats fed an alcohol Lieber-DeCarli diet for 6 weeks reduces hepatic steatosis through downregulation of SREBP-1c and reduction of lipid peroxidation.…”
Section: Metformin and Ampk Activationmentioning
confidence: 99%